THE T MODEL OF APPLYING SOCIAL MARKETING IN HEALTH PROMOTION IN THE REPUBLIC OF MOLDOVA - Alina Timotin (World Science, 2019)
The present work analyses 8 models of social marketing (1984-2008) that appear in the specialised literature. Because each of them presents important elements, here appeared the necessity of an integrative simplified model. The premises for creating the T Model for the implementation of social marketing in the Republic of Moldova are: the need for behavioural change programs, the limited development of social marketing, low knowledge of health specialists on the concept of social marketing, creative but fragmented use of social campaigns to promote a healthy lifestyle. The T Model can be taken over by other countries where the concept of social marketing is not sufficiently promoted and where public health specialists do not have advanced knowledge in this field. The model is a practical tool, described in terms of: the basic principles, the conceptual scheme and the methodological steps of implementation.